Exposição intervalada à aflatoxina B1: um novo protocolo em busca da segurança alimentar - Braga, Ana Claudia Monteiro (2018)
Aflatoxin B1 (AFB1) is the most common and toxic mycotoxin that contaminates food from plantation to consumption. Exposure to AFB1 causes several health problems, from the simplest as food poisoning, to more serious ones such as the development of liver cancer. It also causes changes in the central nervous system, characterizing itself as a great risk to the population. The treatment of the effects and reduction of the contaminations by AFB1 have been a constant subject in the health agencies of the whole world, however, this task has not been enough to protect the populations of underdeveloped countries, which are the most exposed to this contaminant. In the literature, very little can be found about exposure strategies that do not cause or reduce the damages identified, so the objective of this work was to seek a protocol of protection that would guarantee that those who are inevitably exposed to contaminated food matrices can do it as safely as possible. Thus, we develop an intervaled protocol of four AFB1 doses (250μg/kg) separated by a 96-hour interval between each dose, tested in male Wistar rats, to observe if this amount of time was enough for the organism to respond to injuries and aggravations of intoxication. To do this, we evaluated toxicity through weight gain and relative weight of animal organs and performed a battery of behavioral tests – marble burying, nest test, open field, object recognition and splash test - and biochemical - aspartate aminotransferase, alanine aminotransferase, creatinine, albumin, thiobarbituric acid reactive substances, reduced iron antioxidant power, nonprotein thiols, ascorbic acid, Na+, K +-ATPase, catalase and glutathione S-transferase and immunoreactivity of protein kinase C - investigating markers that normally presents alterations even after a short period of time. As a result of this work, we observed that no one of these biological parameters changed, which allows us to propose that with this time interval, for the number of exposures and doses proposed, it is possible to protect the organism reducing the diseases' chance of progression due to a chronic exposure to these mycotoxins.